2019
DOI: 10.1101/858431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Localizing components of shared transethnic genetic architecture of complex traits from GWAS summary data

Abstract: 1Despite strong transethnic genetic correlations reported in the literature for many complex traits, the non-2 transferability of polygenic risk scores across populations suggests the presence of population-specific 3 components of genetic architecture. We propose an approach that models GWAS summary data for one 4 trait in two populations to estimate genome-wide proportions of population-specific/shared causal SNPs. 5In simulations across various genetic architectures, we show that our approach yields approxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 88 publications
0
52
0
Order By: Relevance
“…Prior studies have shown that complex traits and diseases are genetically correlated at different levels between EAS and European (EUR) populations 2123 , but the genetic overlap within EAS populations has not been characterized yet. Leveraging existing GWAS summary statistics from BBJ and UKBB, we investigated the comparative genetic architecture of quantitative traits within EAS (TWB vs. BBJ), and between EAS and EUR populations (TWB vs. UKBB and BBJ vs. UKBB).…”
Section: Mainmentioning
confidence: 99%
“…Prior studies have shown that complex traits and diseases are genetically correlated at different levels between EAS and European (EUR) populations 2123 , but the genetic overlap within EAS populations has not been characterized yet. Leveraging existing GWAS summary statistics from BBJ and UKBB, we investigated the comparative genetic architecture of quantitative traits within EAS (TWB vs. BBJ), and between EAS and EUR populations (TWB vs. UKBB and BBJ vs. UKBB).…”
Section: Mainmentioning
confidence: 99%
“…Tier 2 anc-eQTLs also had nonoverlapping 95% credible sets for each gene but were commonly segregating (MAF ≥ 0.01) in both high and low ancestry groups. This class of anc-eQTLs was identified using PESCA 17 , which accounted for population-specific LD patterns. We identified 109 genes (1.1%) with eQTLs having a posterior probability (PP) > 80% of being specific to AFRhigh and 33 genes (0.4%) matching the same criteria for IAMhigh.…”
Section: Identification Of Ancestry-specific Eqtlsmentioning
confidence: 99%
“…For genes with non-overlapping lead eQTL signals (Figure 3a, left branch), eQTLs from the high group were categorized into Tier 1 anc-eQTLs if they were common variants (MAF >= 0.01) in the high group but rare or absent in the low group. If the eQTLs were common variants in both the high and low groups, their specificity was further assessed using PESCA 17 for differential effect size while accounting for LD between eQTLs. LD pruning on eQTLs with r2 > 0.95 was performed prior to PESCA analysis.…”
Section: Identification Of Egenes Cis-eqtls and Ancestry-specific Cis-eqtlsmentioning
confidence: 99%
“…Initial studies have indicated that the genetic architectures of many complex traits and diseases are concordant between populations -both at the single-variant level and at the genome-wide level. In particular, many genetic associations identified in European populations have been replicated in non-European GWAS, and recent studies have estimated the trans-ethnic genetic correlation between European and non-European populations to be moderate or high for many traits [16][17][18][19] . These findings suggest that the transferability of PRS may be improved by integrating GWAS summary statistics from diverse populations.…”
Section: Introductionmentioning
confidence: 99%